Penerapan Konsep Manajemen Berbasis Mutu Terpadu Pada Taman Kanak-Kanak Islam Terpadu - Adliah Mansur; Mulyawan Safwandy Nugraha; Neng Aulia Farida (Institut Madani Nusantara, 2021)
Early Childhood Education is education given to children in the golden age of children (golden age). Education that is in accordance with its development is very important to pay attention to both in terms of process and outcome because it will affect how children's educational experiences at other levels. Attention in education can be viewed from how integrated quality assurance management or Total Quality Management. Research on Total Quality Management in this article was conducted at TKIT / Creative School Azzahra 1 Cisaaat, Sukabumi Regency. The research was conducted using a qualitative approach, data collection techniques using observation, interviews and documentation study. Based on a comprehensive data analysis on the Application of Integrated Quality Management Concept in TKIT / Creative School Azzahra 1 Cisaat, Sukabumi District starting from Planning, Organizing, Implementing, has been carried out well. This is influenced by supporting factors such as the existence of a clear vision and mission of the institution, structured learning objectives, adequate facilities and teachers. However, things that are considered obstacles include leadership and transparency of operational funds. The evaluation and success rate of the application of the concept of integrated quality-based management at TKIT / Creative School Azzahra 1 Cisaat, Sukabumi Regency are good but must be improved.